2016
DOI: 10.15766/mep_2374-8265.10356
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Evaluating High-Value Care Through a Novel Case-Based Morning Report Curriculum

Abstract: Introduction: It's the responsibility of medical educators to train residents to be responsible stewards of finite health care resources. Thus, we developed an interactive morning report curriculum that focuses on high-value care (HVC) decision making using real-world cases. In addition, we developed a novel evaluation tool to assess residents' application of cost-conscious care principles through the use of an HVC scoring algorithm. Methods: For each HVC morning report session, a resident presents a case that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…In order to prepare medical students to apply HVC concepts when making medical decisions for pediatric patients, we developed an interactive workshop that reviews concepts of HVC, including the Choosing Wisely lists in pediatrics and encouraged thinking of downstream effects of medical decisions. Overall, this workshop has been well received by participants and similar to other studies, [25][26][27][28] participants reported increased confidence and self-assessed competence in providing high-value, cost-conscious care. Students reported that the curriculum improved their knowledge of HVC by pushing them to understand how an intervention changes management and to think about cost and harm.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In order to prepare medical students to apply HVC concepts when making medical decisions for pediatric patients, we developed an interactive workshop that reviews concepts of HVC, including the Choosing Wisely lists in pediatrics and encouraged thinking of downstream effects of medical decisions. Overall, this workshop has been well received by participants and similar to other studies, [25][26][27][28] participants reported increased confidence and self-assessed competence in providing high-value, cost-conscious care. Students reported that the curriculum improved their knowledge of HVC by pushing them to understand how an intervention changes management and to think about cost and harm.…”
Section: Discussionsupporting
confidence: 74%
“…Students reported that the curriculum improved their knowledge of HVC by pushing them to understand how an intervention changes management and to think about cost and harm. However, unlike previously published interventions, [25][26][27] our learners were not told that the case discussion was based in HVC concepts which made it more likely that students gave their initial diagnostic plan unbiased by the idea of HVC. Because the facilitator then prompted them to explain why they were asking for a test or intervention and if and how that changed management, this allowed the students to make new connections between their current thinking and HVC.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Necessary educational resources are available through journal sections on value, 17,18 Choosing Wisely resources, 19 and various other HVC curricula. [20][21][22][23] Despite these resources, data reveal that only 10% of pediatric program directors and 15% of internal medicine residency programs report having a formal curriculum on HVC. 24,25 In a survey of pediatric residency programs, respondents identified the largest barrier to HVC as a lack of cost transparency.…”
Section: Problem Identificationmentioning
confidence: 99%
“…12 In the past decade, we have made progress establishing needed educational resources around HVC with the introduction of journal sections on value, 13,14 the Choosing Wisely campaign, 15 and HVC curricula. [16][17][18][19] Despite this increase in resources, there remains a significant gap in uptake. Several national surveys have found low rates of formal HVC education in internal medicine residency programs.…”
Section: Introductionmentioning
confidence: 99%